PEREMPUAN DALAM SISTEM PEMBERIAN GELAR ADAT MASYARAKAT KERINCI DI DESA PENDUNG TALANG GENTING - Budi Darmawan (Jurnal Budaya Nusantara, 2023)
The purpose of the study was to study and analyze the customary title-giving system of the Pendung Talang Genting village community, the tasks of indigenous leaders given to men instead of women, and community perceptions of it. This research is a descriptive qualitative research, describing and telling about the events in the tradition of awarding traditional titles and the position of women in it, data collected through interviews, newspapers, articles, documents, and others that took place in Pendung Talang Genting village, Kerinci. Traditional titles are given to people who have been selected and given traditional titles in the village. This title is also given to people who have ability and integrity, dare to uphold justice, are valiant, and symbols identified with men, and not women according to the village community. The perception of the community from the descendants of Ninik Mamak and the village community about the granting of traditional titles in the village as a whole responded positively, the community collectively accepted the granting of traditional titles and there was no rejection because it was attached to the traditions and culture of the community